1991
DOI: 10.1007/bf02100194
|View full text |Cite
|
Sign up to set email alerts
|

On the mode of evolution of alpha satellite DNA in human populations

Abstract: The hypothesis that highly reiterated satellite DNAs in present-day populations evolve by molecular mechanisms that create, by saltatory amplification steps, new long arrays of satellite DNA, and that such long arrays are used for homogenization purposes, has been tested both in mouse and in humans. In mouse, the data obtained are consistent with this hypothesis. This was tested in more detail on chromosomes 13 and 21 of the human genome. A Centre d'Etudes du Polymorphisme Humain family, which in some individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Also, it is not our intention to give the ira-pression that the presented data on D. schiavazzii satDNAs can explain all aspects of satDNA evolution in all species. Other mechanisms, such as "saltatory amplification steps" (Mar~ais et al 1991), have also been proposed. Unfortunately, there are no models available that quantify the impact of such processes; thus, they were neglected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is not our intention to give the ira-pression that the presented data on D. schiavazzii satDNAs can explain all aspects of satDNA evolution in all species. Other mechanisms, such as "saltatory amplification steps" (Mar~ais et al 1991), have also been proposed. Unfortunately, there are no models available that quantify the impact of such processes; thus, they were neglected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unreasonable to suggest that these events could also be stimulated by I-R dysgenesis-induced heterochromatic recombination. Interestingly, L1 elements were suggested to be involved in the generation of heterochromatic variability in human chromosomes (40). Further investigations on the interactions between LINEs and heterochromatic regions will be necessary to further clarify the impact of TEs upon heterochromatin evolution in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Marçais et al [45] and Prades et al [44] observed that the block of alphoid DNA at the centromeres of human chromosomes is susceptible to variations in length created by jumping ampli�cation, with an unequal exchange of large alphoid domains between homologous chromosomes, and deletions of large DNA segments. Probably, through a similar mechanism, these Alu-like sequences retrotransposed within the T. torpedo genome to speci�c sites such as telomeric regions that are particularly exposed to a new insertion of transposable elements [46].…”
Section: Characterization Of Repeated Sequencesmentioning
confidence: 99%